Decree No. 109/2013 Amending Certain Provisions of the Executive Regulations Implementing the Building Law Promulgated by the ministry decree No.144/2009 - Egypt (2025)
Ministry of housing and Urban Communities Ministerial decree no. 109 of the year 2013 – وزارة الإسكان والمجتمعات العمرانية قرار وزارى رقم 109 لسنة 2013